Analysis Mooring System Configuration of Submerged Floating Tunnel - Dita Kamarul Fitriyah; Budi Suswanto; Endah Wahyuni (IPTEK Journal of Proceedings Series, 2017)
Submerged Floating Tunnels (SFT) is a tubular structure that is submerged and floating in depth remains through the system of anchors consisting of a cable connected to the seabed. SFT structure imposed its own weight and is assisted by the buoyancy or uplift caused by water, cross sectin of the tunnel is designed so that buoyancy can overcome the structural weight and experienced a lift force that causes the floating structure. Fastening system (mooring system) also play a role which is to inhibit the SFT structure, minimize displacement and stress caused by environmental burden, such as earthquakes and hydrodynamic load that can aggravate the condition SFT structure in case of crossing the sea with SFT system. SFT will give a fairly small impact on the environment as it floated in the water, and with built using a modular system, the SFT (Submerged Floating Tunnels) can reach a distance long enough and does not cause pollution. Basically the same as the force that occurs archimides principle, where the objects are in the water to get a compressive force to the top. Cross sectional analysis SFT, will be modeled by 7 different models that have been in previous studies. The model's of SFT with steel cable to hold the structure in order to remain strong with the inclination selected. Analysis is done by modeling the triangle wiring configuration with different angle of incliflation cable. The analysis by comparing the test model were made earlier with prototype analyzed numerically. The expected structure did not undergo excessive deformation due to the environmental burden. Therefore, the structure of the SFT will be done with the Abaqus as finite element analysis. So, obvious deformation occurred in the cable. Therefore, it was expected to obtain the optimum angle of inclination was 54º.